The Influence of the Dark Triad Personality on Bullying Behavior in Adolescents - Adrianty, Nurul Adha; Firdaus, Faradillah; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Bullying behavior is a behavior that is not prosocial so that it can have a negative effect on both the perpetrator and the victim. This bullying behavior is influenced by certain negative factors. The purpose of this study was to determine the effect of the dark triad personality on bullying behavior in adolescents. Respondents to this study amounted to 100 adolescents with an age range of 13-18 years and had experienced verbal, physical or psychological bullying. The sampling technique in this study used accidental sampling. The measuring tool used is the Olweus Bully/Victim Questionnaire (OBVQ) to measure the bullying variable and the Short Dark Triad (SD3) to measure the dark triad personality variable. This study uses multiple linear regression analysis techniques. The results showed that the dimensions of Machiavellianism and psychopathy had a significant effect on bullying behavior, while the dimensions of narcissism did not have a significant effect. The conclusion of this study is that there is an influence of dark triad personality for aspects of machiavellianism and narcissism on bullying behavior in adolescents.